Possibilities of physiotherapy in Chronic Obstructive Lung Disease - Joanna Chłystek; Julia Pietsch; Aleksandra Czapiewska; Paulina Gąsior; Marta Bielejewska; Karolina Kuźba; Mateusz Łakomski (Kazimierz Wielki University, 2018)
COPD is a progressive disease of the respiratory system that, if untreated, decreases the quality of life of patients. The treatment of COPD is mainly based on the use of bronchodilators and the use of appropriate exercise training. Numerous studies show that properly selected physical effort has a beneficial effect on improving exercise tolerance, spirometric indexes and reducing dyspnoea in patients. Treatments such as: postural drainage, inhalations, chest patting and learning an effective cough also contribute to improving the quality of life in patients suffering from COPD. The appearance of special NIV apparatus very effectively facilitates lung ventilation, and most importantly - allows the patient to support treatment at home.